2014
DOI: 10.7861/clinmedicine.14-3-255
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral amyloid angiopathy: a transient ischaemic attack mimic

Abstract: Cerebral amyloid angiopathy: a transient ischaemic attack mimicCerebral amyloid angiopathy is a commonly occurring condition that is not familiar to most clinicians. A common presenting feature may be transient focal neurological symptoms leading to the potential for clinical misdiagnosis as transient ischaemic attack. This may result in the inappropriate use of anti-platelets and anticoagulants or radiological misdiagnosis. It is also being increasingly recognised as an important cause of spontaneous intracer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Such small hemorrhages are accompanied by an accumulation of Aβ depositions in the tunica media, smooth muscle cells, and adventitia (Charidimou et al, 2012;Brown and Thore 2011). Clinically, pathological changes in vessels in the AD are manifested as cerebral amyloid angiitis (Chung et al, 2011) or more frequently as cerebral amyloid angiopathy (Charidimou et al, 2012;Illsley and Ramadan, 2014), which are responsible for 5-10% of spontaneous intracerebral hemorrhage (Vinters, 1987). Sengillo et al (2013) demonstrated a significant decrease in the number of pericytes and mural vascular cells in the human cortex and hippocampus by 60% and 33%, respectively.…”
Section: Circulatory-system Changes In Neurodegenerative Disordersmentioning
confidence: 96%
“…Such small hemorrhages are accompanied by an accumulation of Aβ depositions in the tunica media, smooth muscle cells, and adventitia (Charidimou et al, 2012;Brown and Thore 2011). Clinically, pathological changes in vessels in the AD are manifested as cerebral amyloid angiitis (Chung et al, 2011) or more frequently as cerebral amyloid angiopathy (Charidimou et al, 2012;Illsley and Ramadan, 2014), which are responsible for 5-10% of spontaneous intracerebral hemorrhage (Vinters, 1987). Sengillo et al (2013) demonstrated a significant decrease in the number of pericytes and mural vascular cells in the human cortex and hippocampus by 60% and 33%, respectively.…”
Section: Circulatory-system Changes In Neurodegenerative Disordersmentioning
confidence: 96%
“… 7 , 38 Avoiding misdiagnosis is crucial, as the administration of anti‐platelet medication and anticoagulants for transient ischemic attacks may increase the risk of CAA‐related ICH. 39 …”
Section: Part 1: Narrativementioning
confidence: 99%
“…Case reports have discussed amyloid spells as seen here, which are often confused as ischaemic events or focal seizures 2 3. The cause of amyloid spells remains unknown but they probably represent either focal seizures due to cerebral irritation from intracerebral haemorrhage, a vasospastic phenomenon or a cortical spreading depression, as in migraine 4…”
Section: Discussionmentioning
confidence: 89%
“…CAA-related inflammation (CAA-RI) is a recently recognised subtype of CAA in which there is neuropathological evidence of CAA-associated vascular inflammation 1. CAA and its inflammatory forms are associated with transient focal events; typically stereotyped migratory sensory-predominant symptoms, often referred to as ‘amyloid spells’ 2–4. We describe a 63-year-old man presenting with what was thought to be capsular warning syndrome, but later diagnosed with CAA-RI, and detail the diagnostic challenge that CAA-RI poses to clinicians as an under-recognised stroke mimic.…”
Section: Introductionmentioning
confidence: 97%